PENGETAHUAN DAN KETERAMPILAN PERAWAT DALAM PELAYANAN KEPERAWATAN HOLISTIK DI INDONESIAN HOLISTIC TOURIST HOSPITAL - Nurul Azizatunnisa; Suhartini Suhartini (Jurusan Keperawatan, Universitas Diponegoro, 2012)
Health care nowadays provides holistic concept, which is focus on client’s healing as the overall objectives including bio-psycho-socio-cultural-spiritual. This concept should be understood and applied by health practitioner, including nurses. Therefore, study about holistic nursing should be done, especially in Indonesian Holistic Tourist Hospital (IHTH) Purwakarta West Java as the first of health provider in Indonesia that used holistic approach. The objective of this research is to describe nurses’ knowledge and skills in holistic nursing care in IHTH. The method of this reseach is decriptive with survey approach. The instrument of the research was using questionnaires with Guttman and Likert’s scale. There were 13 respondents as the samples of the research by using the total sampling. The data were analyzed using univariat to know the level of knowledge and skills to provide holistic nursing care by nurses in IHTH. The result of the research showed that nurses’ knowledge about holistic nursing is divide into three categories: 23,1% high, 69,2% sufficient and 23,1% low. The nurses’ skill to provide holistic environment also divided into three categories: 7,7% well, 76,9% fair dan 15,4% less. The result of observation showed that 13 skill had done by mostly nurses, 12 skill had done by less nurses and 8 skill had done by no nurse. The conclusion of the research showed that the level of nurses’ knowledge and skills in holistic nursing care in IHTH is moderate. Nurses of IHTH should improve their knowledge and skill in holictic nursing care by training or recite about holistic nursing